Inflation, Unemployment, and Economic Growth in a Schumpeterian Economy. (3rd June 2021) - Chu, Angus C.; Cozzi, Guido; Fan, Haichao; Furukawa, Yuichi
Abstract: In this paper, we explore the relationship between inflation and unemployment in a monetary Schumpeterian growth model. Under the cash‐in‐advance (CIA) constraint on research and development (R&D), higher inflation reduces innovation and increases unemployment. Under the CIA constraint on consumption, higher inflation also reduces innovation but decreases unemployment instead. Therefore, the two CIA constraints imply drastically different relationships between inflation and unemployment. This theoretical result is consistent with our empirical finding, and it provides a plausible explanation for the mixed empirical results in the literature. Calibrating our model to aggregate data in the United States and the Eurozone, we also explore the relationship between inflation and unemployment quantitatively.